The National Association of School Psychologists' Self-Assessment Tool for School Psychologists: Factor Structure and Relationship to The National Association of School Psychologists' Practice Model. Issue 2 (2nd April 2016) - Eklund, Katie; Rossen, Eric; Charvat, Jeff; Meyer, Lauren; Tanner, Nick
ABSTRACT: The National Association of School Psychologists' Model for Comprehensive and Integrated School Psychological Services (2010a), often referred to as the National Association of School Psychologists' Practice Model, describes the comprehensive range of professional skills and competencies available from school psychologists across 10 domains. The Self-Assessment Tool for School Psychologists is a two-scale, 48-item self-report measure that is based on the Practice Model and designed to have practitioners assess the degree to which they engage in various professional activities (A scale), and the perceived level of importance of those activities to effective service delivery (B scale). The present study aimed to examine the factor structure and psychometric properties of the Self-Assessment Tool for School Psychologists and to evaluate the proposed interpretation regarding school psychologists' professional practices. Participants included a sample of 1, 293 practicing school psychologists. Results of EFA and CFA, as well as reliability analyses, supported a seven- and five-factor model for the A and B scales, respectively. Collectively, this study suggests a varying factor structure between the Self-Assessment Tool for School Psychologists and the 10 domains of the Practice Model. Implications for conceptualization of school psychological practice in relation to the National Association of School Psychologists' Practice Model and future development of the Self-Assessment Tool for School Psychologists are discussed.